Pride and prejudice: Unraveling and mitigating domestic country bias - Fischer, Peter Mathias; Zeugner-Roth, Katharina Petra; Katsikeas, Constantine S.; Pandelaere, Mario (Journal of International Business Studies, 2022)
Firms pursuing expansion abroad increasingly face challenges of protectionism and discrimination against foreign products, a phenomenon widely recognized as domestic country bias. This research addresses discordant findings in previous work by introducing a new mechanism of domestic country bias that operates distinctly for national identifiers and ethnocentric consumers, connecting these two groups to regulatory focus theory. Using three experimental studies and a survey involving actual product possessions, we provide new evidence that consistently demonstrates that national identity and consumer ethnocentrism are associated with different goals, namely, an approach goal and an avoidance goal, respectively. Importantly, the results reveal that domestic country bias due to national identity can be attenuated by priming a prevention focus, while domestic country bias due to consumer ethnocentrism can be reduced by priming a promotion focus. The findings offer international marketing managers valuable insights into reducing domestic country bias and effectively segmenting international consumer markets. This research is the first to demonstrate how global companies can actively overcome domestic country bias by deploying suitable international marketing programs rather than avoiding specific segments and/or downplaying foreign origins.